The Significance of Plasma Inhibitor(s) in the Control of Fibrinolytic (Plasmin) Activity in Blood - Monkhouse, Frank C.; Milojevic, Susan; Schmitt, Adrianne (Thrombosis and Haemostasis, 1972)
A single one minute wash with three volumes of iso-amyl alcohol will remove all effective antithrombin and antiplasmin activity from plasma. On centrifugation, a clear inhibitor-free plasma with prothrombin activity and with no measurable loss of plasminogen or plasmin is obtained. Studies were carried out on both dog and human plasma. When iso-amyl alcohol treated plasma is stored either at room temperature or at 4° C, the plasminogen in it spontaneously converts to plasmin. The rate at which it does this is proportional to the amount of activator present in the original plasma. When stored at -20° C, this plasmin is stable indefinitely and provides an excellent source of plasmin for routine studies. Experiments in which urokinase was added to plasma samples and the mixture allowed to incubate for varying periods of time from 10 minutes to 15 hours before inhibitor was removed, showed that very little plasmin is destroyed by inhibitor. The plasmin-inhibitor complex is largely reversible. Zone electrophoresis studies indicate that iso-amyl alcohol removes alpha globulins, lipoproteins and some glycoproteins.